Transition management towards sustainable mobility in Alpine destinations: realities and realpolitik in Italy's South Tyrol region - Scuttari, A.; Volgger, M.; Pechlaner, Harald (Routledge, 2016)
Sustainable mobility, including public transport and human-powered slow mobility is a priority for the sustainable development of tourism destinations, but it is a complex challenge to devise, implement and manage. This paper explores the mechanisms and conditions governing transition towards sustainable mobility in destinations, using a complexity-based approach. Destinations are understood as complex adaptive systems where social-ecological, socio-technical and socio-political subsystems interact dynamically with the tourism subsystem. These subsystems are interwoven and undergo significant, and inter-related, changes during transition towards more sustainable mobility. Three examples from the tourism intensive Alpine destination of South Tyrol (Italy) illustrate subsystem interactions during the transition process. Key player interview-based qualitative research indicates that the complexity of transition management is rooted particularly in the paired presence of risk aversion among local stakeholders and the unpredictability of visitor flows. Mitigating risk aversion through collective knowledge creation and offering answers to unpredictability by developing a strong adaptive and (re)organisation capacity seem to be required to adjust sustainable mobility solutions to continuous market changes, to convince stakeholders and to guarantee incremental and durable success. The public sector's special role is noted, as are the time demands of transition management, and the value of both formal and informal partnerships.